(untitled) (Doctor Virtualis, 2024)
Hearsay evidence, despite its evident inadequacy to provide certain knowledge about the events that occurred, has been used in criminal trials since the Early Middle Ages. The essay traces the reflection of medieval legal science, in particular by Bartolo da Sassoferrato, on the formation of the Judge’s conviction, to offer a contribution to understanding the reasons for the use of this anomalous evidence also in contemporary criminal trials.